Autophagy as a barrier to infection - Swanson, Michele (Henry Stewart Talks, 2012)
Autophagosome biogenesis, Autophagy a regulated intersection of the secretory and endosomal pathways, Genetic analysis in yeast has accelerated autophagy research, Autophagy is inhibited by mTOR, Autophagosome biogenesis is coordinated by a cascade of Atg proteins, Autophagosomes mature rapidly in C57Bl/6 macrophages, A wide variety of pathogens encounter the autophagy pathway, Autophagy in infection and immunity, Illustrations: Legionella pneumophila, Shigella flexnerii, Crohns' disease, Mycobacterium tuberculosis, Naip5 NOD-like receptor cytosolic surveillance protein, Inflammasome components coordinate autophagy and pyroptosis as barriers to infection, Autophagy enhances MHCI and MHCII antigen presentation